2003
DOI: 10.1002/app.12548
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic analysis in grease rheology

Abstract: ABSTRACT:Yield stress, and small-and large-amplitude oscillatory shear measurements were performed on greases in a cone-plate fixture. Below the yield point, the grease behavior mimics that of a lightly crosslinked polymer. In large-amplitude oscillations that exceed the yield stress, harmonic distortion appears in the stress waveform. The elastic component of the stress is continuous across the transition, while the viscous, or out-of-phase component, is a transient stress that occurs in the high shear rate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Cyriac et al [18] reported a two-fold reduction of yield stress with a certain temperature increase for both lithium-and polyurea-thickened greases. A decrease in the yield stress of the lithium grease at elevated temperature was reported in Reference [19]. Ide et al [20] found the activation energy based on Arrhenius's law as an appropriate parameter for life prediction of lithium greases.…”
Section: Degradation Systems Of Greasesmentioning
confidence: 92%
“…Cyriac et al [18] reported a two-fold reduction of yield stress with a certain temperature increase for both lithium-and polyurea-thickened greases. A decrease in the yield stress of the lithium grease at elevated temperature was reported in Reference [19]. Ide et al [20] found the activation energy based on Arrhenius's law as an appropriate parameter for life prediction of lithium greases.…”
Section: Degradation Systems Of Greasesmentioning
confidence: 92%
“…Several works on MRG have validated that the settling problem of the iron particles can be eliminated by utilizing grease which has thixotropic properties as a medium [24,25,26]. These properties restrict any reversible flow in the application devices without the presence of external force [27,28]. In addition, some other advantages of MRG include self-sealing, thick viscosity, anti-wear properties, low friction, and robustness to extreme temperatures and pressures [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The application of LAOS has been useful for materials that exhibit strong non-linearities, e.g. dynamics of polymer solutions [15][16][17], flow of concentrated and diluted suspensions [18][19][20][21], biofluids characterization [22], non-linear soft materials [23], presence of yield stress within the viscoelastic behavior [24].…”
Section: Introductionmentioning
confidence: 99%